(untitled) (Research, Society and Development, 2022)
The pharmacist is an essential professional inserted in the expanded nucleus of family health and primary care (NASF-AB), being part of a multiprofessional team, being able to develop exceptional work with the patient and the family. Objective: The research includes reporting the importance of the role of the clinical pharmacist inserted in the NASF-AB, and the care of patients most in need of support and guidance who practice the irrational use of medicines. Methods: The methodology applied to the research was a systematic review, analyzing research in English and Portuguese, using the databases PubMed, Scielo, Lilacs as references. Results: In this study, the increase in drug consumption was greater between 2019 and 2021, where the drugs that underwent a significant increase were psychotropic drugs, such as antidepressants and antipsychotics, linked to fear and sadness symptoms and social isolation, were factors that predispose to irrational use. Conclusion: Pharmacists are professionals trained to provide full drug support to the patient, and during the pandemic it was essential to help control the panic that spread among the population, acting in the promotion, protection and recovery of health and in the rational use of medicines.